Novel DPP derivatives functionalized with auxiliary electron-acceptor groups and characterized by narrow bandgap and ambipolar charge transport properties. (February 2021) - Fusco, Sandra; Barra, Mario; Bonomo, Matteo; Cassinese, Antonio; Centore, Roberto; Chiarella, Fabio; Senneca, Francesco; Carella, Antonio
Abstract: Four novel diketopyrrolopyrrole (DPP) derivatives have been synthesized and characterized: the dyes are based on a DPP electron acceptor core symmetrically functionalized with donor bi-furyl moieties and end capped with four different auxiliary electron-acceptor groups. Because of the alternation along the molecular backbone of electron acceptor and donor groups, all the dyes are characterized by optical absorption maxima approaching or exceeding 700 nm. In the solid state, this optical behavior determines for all the dyes a very low optical bandgap ranging from 1.57 eV to 1.29 eV, while electrochemical characterization shows a clear dependence of the LUMO energies on the strength of the auxiliary electron-acceptor groups. All the dyes are characterized by stable LUMO energies suitable for their application as n-type semiconductors. Organic field-effect transistors based on the reported compounds display actually n-type behavior and, in three cases, a very interesting and balanced ambipolar charge transport behavior was moreover observed. Graphical abstract: Image 1 Highlights: Novel difuryl-DPP derivatives end capped with auxiliary electron acceptor groups have been synthesized and characterized. The optical absorption of the dyes significantly extends in the NIR part of the spectrum. Thin films of the dyes show an extremely low bandgap, up to1.29 eV. Three of the four prepared dyes, used as active layers in OFET, present an ambipolar charge transport behaviour.